Radiometric measurements - Bille, Jean-Claude (International Livestock Centre for Africa, 1984)
Discusses, briefly, the principle of radiometric measurements and presents results of ground measurements on reflectance, grass cover (both green plants & total cover), and grass biomass in Sidamo, Ethiopia. Includes analysis of the correlation of the normalized difference green vegetation index to biomass, green cover & total cover.